Gottes Herrschaft : eine Analyse der Denkschrift (Jes 6, 1-9, 6) - Wagner, Thomas. (Vetus Testamentum, Supplements, 2006)
This volume analyses the so-called 'Denkschrift' (Isa 6:1-9:6) by focussing on the image of God's Reign. It discusses the literary formation and shows that the idea of God's Reign is the red line connecting independent texts in former times. The study focuses on the literary formation and on the images of God's Reign. Subjects included are the investigation of the literary form of Isa 6, comparisons with neo-assyrian prophecies and royal texts from Egypt and the discussion of literary form and origin of the messianic announcement in Isa 9. The final description of the image of God's Reign gives a deeper insight in the development of theological ideas in ancient Israel and is useful for a closer view on Judah's history of religion between the 8th and 5th centuries B.C.E.